The Effect of Coronavirus SARS-CoV-2 in the Tourism Industry in Africa - AKBULAEV, Nurkhodzha; ALIYEV, Vasif (Journal of Environmental Management and Tourism; Vol 11 No 8 (2020): JEMT Volume XI Issue 8(48) Winter 2020, 2021)
This article is designed for identifying the ongoing and future possible impacts on tourism activities due to flare-up of the Coronavirus (known as the new type coronavirus SARS-CoV 2) that occured in Wuhan, China. Writing a summary of the affects of Coronavirus on tourism sector of Africa in 2020 was the objective in this examined article. Second-hand information particularly global news reports released reports from online journals and newspapers was a source for this article. Below-mentioned parts of article are for debate: 1. Global effect of Coronavirus, confirmed cases and death toll in the country, affected area of Coronavirus. 2. Analysis of African economy and tourism industry. 3. Preventative measures for COVİD-19. This study was exposed that however at its early stage, Coronavirus didn't spread widely, but global economy has decreased sharply. Africa has taken preventative measures as well as setted up the fund to meet the difficulties. African people had also great effect on Coronavirus. African government hasn't yet lost it hope to remain stable tourism industry.